Internalization of Akidah Moral Values and Learning Motivation of Students in Madrasah Tsanawiyah - Hanisa Hanisa; Arifuddin Arifuddin; Andi Arif Pamessangi (Journal of Indonesian Islamic Studies, 2023)
This study aims to examine efforts to internalize the values of moral creed to students in Madrasah Tsanawiyah Salobongko; and knowing efforts to increase student motivation in Madrasah Tsanawiyah Salobongko. The type of research used is qualitative research. Data collection techniques use interviews, observation, and documentation techniques. The data analysis techniques are data reduction, data presentation, and verification of conclusions. The results of this study show that: 1) Efforts to internalize the values of creed carried out by teachers in students, namely by instilling an attitude of pleasure, obedience, obedience, and discipline in carrying out the commands of Allah Swt., while efforts to internalize moral values carried out by teachers in students are by example, habituation, advice, and reprimand. 2) Efforts made by teachers in increasing student motivation in Madrasah Tsanawiyah Salobongko include using various methods and providing opportunities for students to interact, such as asking and answering, giving praise, and giving reprimands and advice.